Dielectric, pyroelectric and polarization behavior of polyvinylidene fluoride (PVDF) - Gold nanoparticles (AuNPs) nanocomposites. (August 2019) - Kushwah, Mamta; Sagar, Rohan; Rogachev, A.A.; Gaur, M.S.
Abstract: In this study, the polymorphism of poly (vinylidene fluoride) (PVDF) was control by gold nanoparticles (AuNPs). Simple one step method was used for synthesis of AuNPs using HAuCl4 ·3H2 O, and N, N-dimethylformamide (DMF). The AuNPs of size 20–30 nm have been prepared by chemical method. DMF was act as reducing agent and solvent of PVDF. The circular samples of diameter 3.5 cm and thickness 10–25 μm were prepared. It has been observed that AuNPs modify the structural morphology of PVDF. The β-phase of PVDF was modified due to interaction between electric charge at the surface of AuNPs and CF2 dipoles. This is further verified by increase of remanent polarization in P-E loop. XRD spectra address the crystallographic phase identification of PVDF in presence of AuNPS. The AuNPs in PVDF matrix significantly enhances 72.2% expansion of remanent polarization (Pr ), 19.23% depletion of coercive field (Ec ) and 70–100% expansion of shifting speed of the ferroelectric polarization. Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD) of pristine and NPs mixed PVDF illustrates the structural properties and reason of enhanced ferroelectric properties. Highlights: Synthesis of AuNPs by DMF as a reducing and capping agent. AuNPs extensively explored and enhances the β-phase of PVDF. Interfacial polarization is main component of dielectric strength of PVDF-AuNPs nanocomposites. AuNPs concentration increases the remnant polarization and coercive field of PVDF. Pyroelectric figure of merit varies from 9.5 to 32.5 μ C m −2 K −1 .